Analisis Penerapan Green Accounting Pada Pengelolaan Limbah dengan Perspektif Maqasid Syariah di RSUD Raden Mattaher Jambi - Della Aliah; Elyanti Rosmanidar; Ferri SaputraTanjung (Tasyri' : Jurnal Muamalah dan Ekonomi Syariah, 2026)
This study aims to analyze the implementation of environmental accounting (green accounting) in waste management at RSUD Raden Mattaher Jambi from the perspective of maqasid shari’ah, identify the obstacles encountered, and examine the efforts undertaken by the hospital to improve environmental accounting practices. This research employed a qualitative approach with a descriptive method. Data were collected through interviews, observations, and documentation involving the Head of Environmental Health Unit, Head of Accounting Subdivision, waste management staff, accounting staff, and the Person in Charge of Hazardous and Toxic Waste (B3) Management. Data were analyzed through data reduction, data presentation, and conclusion drawing. The results indicate that RSUD Raden Mattaher Jambi has implemented medical, non-medical, and liquid waste management in accordance with established procedures and has allocated various environmental management costs. However, the implementation of environmental accounting has not been fully optimized because environmental costs are still combined with general operational expenditures and are not separately disclosed in financial reports. From the maqasid shari’ah perspective, the implementation reflects the principles of hifz al-nafs, hifz al-‘aql, and hifz al-nasl, but has not fully fulfilled the principle of hifz al-mal due to the absence of specific classification and reporting of environmental costs. The main obstacles include limited waste treatment technology, the absence of environmental cost classification, limited human resources, weak internal coordination, and the lack of internal regulations related to environmental accounting. Efforts undertaken by the hospital include strengthening coordination among units, improving human resource competencies, separating environmental budgets, developing standard operating procedures for environmental cost recording, and planning the adoption of environmentally friendly technologies.